Mechanical characterization using optical fiber sensors of polyester polymer concrete made with recycled aggregates - Reis,João Marciano Laredo dos (2009)
The sustainable management of solid wastes encourages metallurgic and metal-mechanic industries to look for safety applications for their wastes, thereby attenuating the environmental impact or lowering the costs. The study herein proposes strain monitoring the recycling of foundry sand with organic pollutants, as inert, in the manufacturing process of polymer concrete using optical fiber sensors. This work also analyzes the compressive strength of polyester polymer concrete made with foundry waste, i.e., recycled foundry sand and polyester polymer concrete made with fresh sand. The foundry sands are contaminated with Sodium Silicate from the mould-making process. Polymer Concrete (PC) is a composite material in which the binder consists entirely of a synthetic organic polymer. Optical fiber sensors present a great deal of potential in monitoring the structural health condition of materials. Experimental results show that the use of the embedded FBG sensor can accurately measure strain, providing information to the operator that the structure is subjected to failure. Multiplexed FBG strain sensors enable measuring strain in different locations by occupying only one tiny optical fiber.